3y^2-6y+3+6y
3y^2=-3
y^2=-1 нет решения
А) х=870 б) х=424 в) х=21 г) х=124
Это правельно. Мы уже розвязывали по алгебре.
(х^8)'=8•х^7
(х^-11)'=(-11)•х^(-12)
(х²/³)'=2/3•х^(-1/3)
(х^(-4/5))'=-4/5•х^(-9/5)
(1/х¹°)'=-10•х^(-11)
((1-3х)⁴)'=4•(1-3х)³•(1-3х)'=-12(1-3х)³
((4х-3)^(-6))'=(-6)•(4х-3)^(-7)•(4х-3)'=-24(4х-3)^7
(1/⁴√(х/2-3)³)'=-3/4•(х/2-3)^(-1/4)•(х/2-3)'=
-3/8•(х/2-3)^(-4)
А) 150:100*50= 75+150 = 225
100*2=200 225>200
б) 100:2=50 150:100*60=90 150-90=60
50<60
в) 1a:2=0,5a 1,2:100*40=0,48a 1,2a-0,48a=0,72a
0,5a<0,72a
г) 2,5b<3b
(250:100*b < 2:2=1 2+1=3 )